Предмет: Алгебра, автор: fnnf102000

решитееееееееееееееееееееееееееее

Приложения:

Ответы

Автор ответа: Аноним
0
1) х^2 + 17х + 72 = ( x + 8 )( x + 9 )
D = 289 - 288 = 1 ; VD = 1
x1 = ( - 17 + 1 ) : 2 = - 8
x2 = ( - 17 - 1 ) : 2 = - 9
2) ( x + 8 )( x + 9 ) = ( x + 9 )( x - a )
Ответ а = ( - 8 )
Автор ответа: zhenyaM2002
0
Разложим первую часть уравнения на множители:
х²+17х+72= х² + 8х +9х +72 =
 =х(х+8) +9(х+8) = (х+9)(х+8)
Приравняем ко второй:
(х+9)(х+8) = (х+9)(х-а)            |÷ (x+9)
x+8=x-a
a=x-x-8
a=-8

Ответ: а= -8.

Похожие вопросы